Pore Mn2+ dynamics of the rhizosphere of flooded and non-flooded rice during a long wet and drying phase in two rice growing soils. (September 2015) - Haque, K.M. Shamsul; Eberbach, Philip L.; Weston, Leslie A.; Dyall-Smith, Mike; Howitt, Julia A.
Highlights: Soil pore Mn 2+ concentrations were higher in flooded soil than in saturated soil. After rice harvest, Mn 2+ concentrations remained high for at least one week. Concentrations of Mn 2+ were generally higher in red sodosol than in grey vertosol. Two peaks of Mn 2+ were recorded: at 4 weeks after flooding and during rice flowering. In the post-flooded, drying stage, the oxidation of Mn 2+ was slower at greater depths. Abstract: Flooded rice soils produce elevated concentrations of soluble manganous manganese (Mn 2+ ) that could be potentially toxic to subsequent crops. To provide insight into how soil pore Mn 2+ changes its concentration in a rice and post rice drying soil, we used an artificial microcosm system to follow Mn 2+ concentrations in two different soil types (red sodosol and grey vertosol) and under two irrigation regimes (flooded and saturated). Soil pore water was collected from four different depths of soil (2.5 cm, 7.5 cm, 15 cm and 25 cm) and Mn 2+ concentrations were analysed during and after the rice phase over a one year cycle. Mn 2+ increased with the advancement of anaerobic conditions at all soil depths, but the concentration was higher in flooded soil compared to saturated soil. Initially, the highest concentration of Mn 2+ was found at a depth of 7.5 cm, while at the later stage of rice growth, more Mn 2+ was found in the deepest sampling depth (25 cm). Plants grown in saturated soils showed a delay in flowering of approximately 3 weeks compared to flooded cultures. Moreover, plants grown in flooded soil produced more tillers and leaf area than those grown in saturated soil. Peak concentrations of soil Mn 2+ were associated with the reproductive stage of rice growth. Mn 2+ concentrations decreased after drainage of water. In post rice soils, Mn 2+ remained elevated for some time (lag phase), and then rapidly declined. Regression analysis revealed that the process of oxidation of Mn 2+ to Mn 4+ following water drainage decreased with soil depth.